Sustainable groundwater management - problems and scientific tools - Haknazarova, Dilobar; Murodullaev, Bakhtiyor (MMIT Proceedings, 2025)
Although groundwater accounts for only 20% of the planet's freshwater reserves, its importance is enormous. This is due, firstly, to its high suitability for drinking, and secondly, it serves as a stable source of water, especially in arid regions. Although groundwater has the property of being stored in large quantities, the most important factor for sustainable management is the rate at which it is renewed. Approximately 800 km3 of groundwater is used annually, which seems to be less than the level of global renewal, but these figures obscure problems at the regional level [1-2]. For example, about 25% of extracted water comes from non-renewable resources. Global averages can also misrepresent the level of pollution. In reality, the situation differs dramatically in each river, spring, or well. Overpumping and pollution of water can lead to the degradation of groundwater, and even to the complete cessation of its use. Due to the limited possibilities of artificial renewal, it is necessary to use this resource carefully and efficiently.